SERVICE ON THE GO (SERVEGO): Online Service Booking Application - Kamaludin, Hazalila; Song, Ho Kai; Mohd Safar, Noor Zuraidin; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2020)
Service On The Go is an online service booking application developed to provide users with access to multiple services in electrical repair, electrical wiring, plumbing repair services, and online home maintenance. Besides, this application also provides a platform for users who are experts in their services areas to promote and share their skills through the Internet. The purpose of ServeGo is to allow the user to find the contact of the person who provides the repair services. It also can solve the problem of the handyman who is facing the difficulty to promote and share their services. Hence, the application can save the time of users who need the services immediately. The app is developed by using Android Studio and Firebase. Android Studio is an official integrated development environment (IDE) for Android application development while Firebase is a service that enables helping the user to manage the centralized database via the cloud. The modules which are notification module, request module, booking status module, payment module, rating module, GPS module are added to implement the application.